2012
DOI: 10.1158/1535-7163.mct-12-0640
|View full text |Cite
|
Sign up to set email alerts
|

Dll4-Fc, an Inhibitor of Dll4-Notch Signaling, Suppresses Liver Metastasis of Small Cell Lung Cancer Cells through the Downregulation of the NF-κB Activity

Abstract: Notch signaling regulates cell-fate decisions during development and postnatal life. Little is known, however, about the role of Delta-like-4 (Dll4)-Notch signaling between cancer cells, or how this signaling affects cancer metastasis. We, therefore, assessed the role of Dll4-Notch signaling in cancer metastasis. We generated a soluble Dll4 fused to the IgG1 constant region (Dll4-Fc) that acts as a blocker of Dll4-Notch signaling and introduced it into human small cell lung cancer (SCLC) cell lines expressing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Cell lysate (15 mg/lane) was separated by SDS-PAGE. Immunoblotting was conducted as previously described (41).…”
Section: Western Blottingmentioning
confidence: 99%
“…Cell lysate (15 mg/lane) was separated by SDS-PAGE. Immunoblotting was conducted as previously described (41).…”
Section: Western Blottingmentioning
confidence: 99%
“…14,15 Several preclinical xenograft studies have shown that Dll4/ Notch blockade inhibited tumor progression by promoting the hyperproliferation of endothelial cells, which resulted in an increase in vascular density but a decrease in functional patent tumor vasculature. [16][17][18][19][20] In addition to the effects of Dll4 blockade on tumor vasculature, Dll4/Notch inhibition is known to reduce cancer stem cells (CSCs), which are an important cancer cell population for malignant tumor progression. 21 Therefore, Dll4 is now recognized as a promising target for improved efficacy in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combination treatment with VEGF and Dll4 inhibitors has demonstrated a more effective regression of tumor vessels and inhibition of tumor progression in several cancer xenograft models compared to VEGF or Dll4 blockade alone. [14][15][16][17][18][19][20] Based on this scientific evidence, we developed HD105, a bispecific antibody that targets VEGF and Dll4 simultaneously. This bispecific antibody consists of an anti-VEGF bevacizumab-similar IgG backbone linked with a Dll4-binding singlechain Fv.…”
mentioning
confidence: 99%
“…Dysregulation of Notch receptors, ligands, or target genes is noted in various cancer cells (1,2). Notch signaling inhibition has been demonstrated to attenuate cancer cell proliferation/cell cycle progression, to decrease cancer cell viability, and to increase cell apoptosis in various types of cancer (1,(3)(4)(5)(6). Furthermore, Notch signaling inhibition is proposed as an alternative adjuvant therapy for radiotherapy and chemotherapy (7,8).…”
Section: Introductionmentioning
confidence: 99%